2009
DOI: 10.1002/ejlt.200900022
|View full text |Cite
|
Sign up to set email alerts
|

Physical‐chemical characteristics and oxidative stability of oil obtained from lyophilized raspberry seed

Abstract: Fresh raspberry (Rubus idaeus), cultivar Willamette, was freeze-dried (lyophilization). A byproduct of lyophilization is "fine dust" of raspberry consisting of finely ground raspberry fruit body and seed. The seeds were separated. The seed oil was isolated and its physical and chemical characteristics were determined. Parameters that characterize the seed and quality of the oil were examined, including fatty acid composition, oxidative stability under different storage conditions, and radical-scavenging activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…Szterk et al obtained similar results of OSI (average 5 h) of camelina oils to those presented in this study by the Rancimat test at the temperature of 100°C. Other authors, e.g., Rudnik et al and Sucurovic et al , reported different values of OSI, due to different Rancimat methods, varying degrees of oxidation of the tested oils (PV, AV), and different fatty acid compositions. The results of the Rancimat method showed a low oxidative stability of tested oils, from 3.47 h for linseed oil to 6.18 h for camelina oil, which is largely associated with a significant (57.1–76.4%) content of polyunsaturated fatty acids.…”
Section: Resultsmentioning
confidence: 94%
“…Szterk et al obtained similar results of OSI (average 5 h) of camelina oils to those presented in this study by the Rancimat test at the temperature of 100°C. Other authors, e.g., Rudnik et al and Sucurovic et al , reported different values of OSI, due to different Rancimat methods, varying degrees of oxidation of the tested oils (PV, AV), and different fatty acid compositions. The results of the Rancimat method showed a low oxidative stability of tested oils, from 3.47 h for linseed oil to 6.18 h for camelina oil, which is largely associated with a significant (57.1–76.4%) content of polyunsaturated fatty acids.…”
Section: Resultsmentioning
confidence: 94%
“…Lyophlization has been previously employed for the preservation of mushroom mycelial culture (Singh et al 2004); however, to the best of our knowledge, this technique has not been used for the storage and maintenance of the fruiting bodies of truffles or mushrooms. Other vegetables have been freeze-dried in order to preserve the composition and properties, for instance, the carotenoid content (Addis et al 2009), the antioxidant properties (Sucurovic et al 2009), the microbiological quality (Tejada et al 2008), or the functional properties (Hu et al 2010), among others. Apparently, the evolution of the aroma intensity and profile has not been previously analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…A validated method for IsoPs was described by Medina et al [30]. [34] or hexane [33,35] in a Soxhlet apparatus for 5e6 h. Afterwards, the solvent is evaporated either under nitrogen gas or in a vacuum evaporator [34,35]. Oil is extracted from the samples through repeating washing with chemical solvent by reflux in Soxhlet apparatus so the solvent can be used repeatedly and the whole extraction process is automatic.…”
Section: Mammalian Samplesmentioning
confidence: 99%
“…Oil is extracted from the samples through repeating washing with chemical solvent by reflux in Soxhlet apparatus so the solvent can be used repeatedly and the whole extraction process is automatic. Also, depending on the size of the Soxhlet apparatus, the amount of samples used for the extraction can vary from less than 10 g to 100 g [34] allowing the extraction of lipids from samples with low lipid content. However, this method takes a long period of time to extract the lipids from the samples and some of the researchers argued that the heating process during reflux in Soxhlet extraction may cause degradation of lipids that are prone to peroxidation such as PUFA, especially DHA [36].…”
Section: Mammalian Samplesmentioning
confidence: 99%